(untitled) (Педагогіка вищої та середньої школи, 2008)
In this article it is necessity and efficiency of the use of sporting tourism as facilities of physical education of students. A purpose and functions of sporting tourism open up. The detailed analysis of scientifically-methodical principles of successful realization of educational and training process is done in the system of physical education.